The Nexus between Renewable Energy, Economic Growth, and Carbon Dioxide Emissions: Evidence from MS-VAR and MS-Granger Causality Methods - Ayça Büyükyılmaz Ercan; Metehan Ercan (Ekonomi, Politika & Finans Araştırmaları Dergisi)
This study aims to examine the dynamic relationship between carbon dioxide (CO2) emissions, renewable energy consumption, and economic growth in Denmark, Sweden, and Chile. These countries were not randomly selected. They were chosen since they have the highest scores according to the Climate Change Performance Index (2023). In addition, Markov-switching vector autoregressive (MS-VAR) and Markov-switching Granger (MS-Granger) causality methods are applied to the annual data of the three countries over the period 1971–2021. Contrary to linear methods, MS-VAR and MS-Granger causality approaches allow us to estimate and interpret this relationship for different regimes, such as recession and expansion. These methods also provide insights into the likelihood and duration of the persistence of the current economic regime. The empirical results show that there is a two-way MS-Granger causality between renewable energy consumption and economic growth in all regimes for the three countries except for moderate and high expansion regimes for Chile. Moreover, in general, there is a two-way MS-Granger causality between economic growth and CO2 emissions in all regimes. Furthermore, the findings from the estimated models indicate that there is a two-way MS-Granger causality between renewable energy consumption and CO2 emissions in general, except for the second regime for Chile.